1975
DOI: 10.1051/rnd:19750222
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Progestagens and Photoperiodism in Improving the Reproductive Rate of the Ewe

Abstract: SUMMARYA brief description of an intensive unit in which Finnish Landrace x Dorset Horn ewes are bred to Suffolk rams every 205 days, to produce lambs which are abruptly weaned at four weeks of age on to cereal-based diets, is given. The unit combines photoperiodism and hormone treatment for the induction and synchronisation of oestrus respectively. The photoperiod treatment consists of an abrupt increase in daylength to i8 hours at 6 0 days of gestation followed by a daily reduction of 3 r/z mn from 90 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

1980
1980
1982
1982

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Lamb production following matings within the breeding season is further limited by low ovulation rates (Hulet & Foote, 1967) and failures of fertilization and embryonic death (Edey, 1969(Edey, , 1976. Robinson, Fraser & McHattie (1975), using a combination of treat¬ ments, including controlled photoperiod, early weaning and pregnant mares' serum gonadotrophin (PMSG) injections, successfully eliminated seasonality and maintained a high level of lamb production from Finnish Landrace Dorset Horn ewes bred at 7-month intervals. How¬ ever, reproductive performance was measured only in terms of conception rates and lambing percentages, and the factors limiting production under these conditions could not be assessed.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lamb production following matings within the breeding season is further limited by low ovulation rates (Hulet & Foote, 1967) and failures of fertilization and embryonic death (Edey, 1969(Edey, , 1976. Robinson, Fraser & McHattie (1975), using a combination of treat¬ ments, including controlled photoperiod, early weaning and pregnant mares' serum gonadotrophin (PMSG) injections, successfully eliminated seasonality and maintained a high level of lamb production from Finnish Landrace Dorset Horn ewes bred at 7-month intervals. How¬ ever, reproductive performance was measured only in terms of conception rates and lambing percentages, and the factors limiting production under these conditions could not be assessed.…”
Section: Introductionmentioning
confidence: 98%
“…How¬ ever, reproductive performance was measured only in terms of conception rates and lambing percentages, and the factors limiting production under these conditions could not be assessed. The aim of the present work was to investigate ovulation rates, the subsequent development of embryos and fetuses and the associated changes in the concentrations of progesterone in the peripheral plasma of the ewes that were used in the studies of Robinson et al (1975).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in which Finnish Landrace Dorset Horn ewes were kept under artificial daylength conditions and weaned after 1 month of lactation (Robinson, Fraser & McHattie, 1975) showed that conception rates of about 90% and litter sizes greater than 2 could be obtained consistently in a breeding programme involving a 7-month interval between lambings. This interval was achieved by the synchronization of oestrus using intravaginal pessaries impregnated with pro¬ gestagen.…”
Section: Introductionmentioning
confidence: 99%
“…In (Robinson et al 1975). Differences in prolificacy between the two lighting regimes were not significant. Fecundity followed the pattern of fertility (Table 4 …”
mentioning
confidence: 95%
“…1918;Fairnie et aL l9l6, 1977;Fukui and Roberts 1977;Gordon 1910Gordon , 1913Gordon , 191 5 , 1911Hackett and Robertson I 980;Haresign 1976;Jennings 1975;Lightfoot et al 1976;Mauleon and Le Provost 1975;Robinson 1965;Thimonier and Cognie 1977;Trounson et al 1916). However, only limited information on the application of these procedures to sheep continuously maintained indoors year-round under controlled lighting is available (Hackett et al 1979; Hackett et al l98l; Hackett and Wolynetz l98l; Robinson et al 1975 (Heaney et al 1980 Although these variables are discrete and not normally distributed, probability levels obtained in this manner should approximate the correct probability levels (Gabriel 1963;Li 1964 (19) l5 (28) 29 (l-s) s2 ( l3) 7 11) 0 03) l 38 (37) 84 (17) 75 (15) 52 (20) 65 (l9) 21 (28) s4 (rs) 126 (13) l0 ( l7 (Gordon 1975). Other studies on our sheep flock have also shown that PMSG does not increase fertility in FGA-treated ewes bred by natural mating (Hackett and Wolynetz l98l , 1982 (Table 6) and 47o in the sixth experiment.…”
mentioning
confidence: 99%